Estrogen to Progesterone Ratio and Fluid Regulatory Responses to Varying Degrees and Methods of Dehydration - Gabrielle E. W. Giersch; Gabrielle E. W. Giersch; Nisha Charkoudian; Margaret C. Morrissey; Cody R. Butler; Abigail T. Colburn; Aaron R. Caldwell; Aaron R. Caldwell; Stavros A. Kavouras; Douglas J. Casa (Frontiers Media S.A., 2021)
The purpose of this study was to investigate the relationship between volume regulatory biomarkers and the estrogen to progesterone ratio (E:P) prior to and following varying methods and degrees of dehydration. Ten women (20 ± 1 year, 56.98 ± 7.25 kg, 164 ± 6 cm, 39.59 ± 2.96 mL•kg•min−1) completed four intermittent exercise trials (1.5 h, 33.8 ± 1.3°C, 49.5 ± 4.3% relative humidity). Testing took place in two hydration conditions, dehydrated via 24-h fluid restriction (Dehy, USG > 1.020) and euhydrated (Euhy, USG ≤ 1.020), and in two phases of the menstrual cycle, the late follicular phase (days 10-13) and midluteal phase (days 18-22). Change in body mass (%BMΔ), serum copeptin concentration, and plasma osmolality (Posm) were assessed before and after both dehydration stimuli (24-h fluid restriction and exercise heat stress). Serum estrogen and progesterone were analyzed pre-exercise only. Estrogen concentration did not differ between phases or hydration conditions. Progesterone was significantly elevated in luteal compared to follicular in both hydration conditions (Dehy-follicular: 1.156 ± 0.31, luteal: 5.190 ± 1.56 ng•mL−1, P < 0.05; Euhy-follicular: 0.915 ± 0.18, luteal: 4.498 ± 1.38 ng·mL−1, P < 0.05). As expected, E:P was significantly greater in the follicular phase compared to luteal in both hydration conditions (Dehy-F:138.94 ± 89.59, L: 64.22 ± 84.55, P < 0.01; Euhy-F:158.13 ± 70.15, L: 50.98 ± 39.69, P < 0.01, [all •103]). Copeptin concentration was increased following 24-h fluid restriction and exercise heat stress (mean change: 18 ± 9.4, P < 0.01). We observed a possible relationship of lower E:P and higher copeptin concentration following 24-h fluid restriction (r = −0.35, P = 0.054). While these results did not reach the level of statistical significance, these data suggest that the differing E:P ratio may alter fluid volume regulation during low levels of dehydration but have no apparent impact after dehydrating exercise in the heat.